Sequencing effects of small-sided games and high-intensity interval training on physical and physiological performance of young soccer players during pre-season - Kharatzadeh Masoud; Morgans Ryland; Thapa Rohit K.; Oliveira Rafael; Faramarzi Mohammad (Biomedical Human Kinetics)
Study aim: This experimental study investigated the sequencing effects of a small-sided games (SSG) protocol and highintensity interval training (HIIT) on the physical and physiological performance adaptation of soccer players, conducted over a fourteen-week of the pre-season.